Brand resignification and fast fashion: new perspectives for promoting sustainability - Seibel, Vanessa de Mello (2023)
The objective of this study is to examine the current perspectives for the introduction of sustainability by brands in the fashion industry, through the analysis of the fast fashion model. Therefore, possible signs of updating the traditional brand model will be exposed in order to identify the transformation of the meaning of brands and the possibility of convergence between the sustainability dimensions. The deductive method and the specific procedure method were used as an approach method, using the bibliographic research method. The research made it possible to conclude that there is progress in the performance of brands on the way to their redefinition by promoting the environmental dimension of sustainability.